Entrepreneurship and engineering - Bardaie, Mohd Zohadie (The Association for Engineering Education In Southeast Asia, East Asia and the Pacific, 1989)
Entrepreneurship has been identified as the driving force behind our development towards the twenty-first century. However, it is argued that entrepreneurship cannot be instantly cre~ted. It is a complex combination of learned individual abilities and more general attitudes to change. One way of understanding entrepreneurship is to look at entrepreneurial behaviour. The paper then discusses the relationship between entrepreneurship and engineering. Emphases are devoted toward the roles that engineers can play in the field of entrepreneurship.